Achieving quality teaching in developing countries : identifying factors that influence the delivery of quality teaching in primary schools in rural Cambodia : a research project presented in partial fulfilment of the requirements for the degree of Master of International Development, Institute of Development Studies, Massey University, Manawatu, New Zealand - Arnold, Denise Joy (The Author, 2015)
At a global level the Education for All focus has shifted from years of schooling to the quality of education being attained. The delivery of quality education is dependent upon quality teaching. While there is no clear definition of quality teaching there are recognised characteristics which lend themselves to quality teaching and therefore are used as proxies to identify what constitutes a quality teacher. Of importance to this study is the fact these same recognised characteristics of what constitutes quality teaching and a quality teacher are reflected in the Ministry of Education, Youth and Sport in Cambodia (MoEYS) goals and teachers in Cambodia clearly identify with these characteristics. Drawing on a case study of Cambodia this research examines the influences that work upon a teacher to either positively influence the delivery of quality teaching or to negatively influence the same. While influences which positively and negatively impact quality teaching are wide ranging, some are definitely more influential than others. Hence there is a clear recognition of the importance of the provision of basic resources for education. The delivery of quality teaching requires basic physical infrastructure and resources such as teacher training, adequate teacher salaries and teaching materials. Without these basic resources a teacher is destined to fail in the delivery of quality teaching. This is particularly relevant in a developing country where the teachers are more likely to be working at a pre-professional level in terms of teaching skills, dependent upon teaching materials and reliant on basic classroom management skills. This is the case in Cambodia. Before any other influences become significant these fundamental needs must be met. There is also an important link between the health of both teachers and children and the delivery of quality teaching. Basic health needs must be met if the delivery of quality teaching is not to be undermined.
Keywords: Effective teaching; Developing countries; Cambodia